Republic of Slovenia : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2003 Article IV Consultation highlights that economic growth in the Republic of Slovenia slowed during 2001-02 to about 3 percent, owing to a weak external environment and subdued domestic demand. Export growth slowed as demand from the European Union weakened, but the impact was cushioned by a rapid expansion of exports to southeastern Europe and Russia. With imports growing more slowly than exports and the terms of trade improving, the external current account swung into surplus in 2001 and strengthened further in 2002, reflecting a satisfactory competitive position.